Perbandingan Kapasitas Inflitrasi Antara Tanah Terkelola Secara Organik Dan Konvesional - Zebua, Bernardus; Gea, Erwin Saputra (Jurnal Ilmu Pertanian dan Perikanan, 2024)
This research compares soil infiltration capacity on organically and conventionally managed land to determine the impact of management on soil quality and sustainability. Measurements were carried out using a double ring infiltrometer at two different locations with similar soil characteristics. The results showed that organic soil had a significantly higher infiltration capacity compared to conventional soil. This is related to the higher organic matter content and better soil structure on organic land. Higher infiltration capacity supports better soil water balance, reduces the risk of erosion, and increases resilience to climate change, making organic management a more sustainable option in agricultural practices. It is hoped that these findings can support the development of agricultural policies that are oriented towards environmental sustainability.